Synthesis of Metallo-Supramolecular Polymers Using 5,5′-Linked Bis(1,10-Phenanthroline) Ligands - Hossain, Md. Delwar; Higuchi, Masayoshi (Synthesis, 2013)
5,5′-Linked bis(1,10-phenanthroline)s were synthesized as new bidentate ligands by a palladium-catalyzed Suzuki-type cross-coupling reaction. Coordination of the ligands to Cu(II), Ni(II), Ag(I), and Zn(II) ions resulted in metallo-supramolecular polymer formation. The 1:1 complexation of the ligands and the metal ions was confirmed by UV-vis titration experiments. The high molecular weights of more than 105 Da, caused by the high complexation constants, were confirmed by the SEC-Viscometry-RALLS method.
Keywords: bis(1,10-phenanthroline)s; metallo-supramolecular polymers; complexation; cross-coupling; palladium